Quercetin: Nutritional and beneficial effects in poultry. Issue 2 (20th April 2017) - SAEED, M.; NAVEED, M.; ARAIN, M.A.; ARIF, M.; ABD EL-HACK, M.E.; ALAGAWANY, M.; SIYAL, F.A.; SOOMRO, R.N.; SUN, C.
Abstract : Flavonoids are natural compounds derived from fruits, vegetables and medicinal plants. These compounds have been reported to possess various biological actions including anti-inflammatory, antioxidant, growth promoter, antiviral, hepatoprotective, antibacterial, antiallergic, anticarcinogenic, antithrombotic and immunomodulator activities in various animals and poultry species. Quercetin is found in various foods such as vegetables, tea, fruits, wine apples and onions and is known to exert positive effects on poultry production and health. Since, quercetin enhances the immune system by stimulating lymphocytes, macrophages and IgY antibody production and improving natural killer cell activity, lymphoid organs (spleen, thymus and bursa) weights as well as activating the cytokines profile, its supplementation can lead to a state of immune alertness and a lower incidence of infections and diseases. In addition, it affects the dendritic cells (DCs) that play an important role in adaptive and innate immunity. Quercetin revokes the ability of lipopolysaccharide (LPS)-stimulated dendritic cells to induce specific T cell activation and reduce the cytotoxicity in both in vivo and in vitro studies, suggesting quercetin works as an immunosuppressive agent. As immune function is crucial for poultry productivity and prosperity, this review elucidates the potential nutritional effects and health benefits of quercetin on poultry as a replacer for traditional immune boosters and growth promoters. It includes the antiviral activity of quercetin against influenza A virus, rhinovirus (caused common cold), adenovirus (source of necrotic pancreatitis in broilers) and suggests its role in counteracting heavy metal toxicity. However, further studies on molecular basis are required to understand mode of action, beneficial applications as a natural feed additive, growth promoter and immune enhancer, beside the side effects of this compound in poultry.